Reducing the rust defect rate of K59 cap fuel filler products in the progressive pressing line using the DMAIC method - Ramadhan, Wanda Gilang; Intani, Arvita Emarilis; Prasetyo, Sutrisno Aji (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to find out how to apply the method to help analysed problems, identify the causes of problems in the production of Cap Fuel Filler K59 at Company defect level in production results. Determining the selected data using purposive techniques. Data collection was carried out by collecting primary and secondary data through literature studies, field studies, observations, interviews and documentation. The data analysis procedure was carried out using the DMAIC method (define, measurement, analyze, improvement and control). After data analysis, improvement efforts are carried out with the following actions: (1) making special placements for re-delivery parts; (2) changing the plastic layer to paper as a base that covers the surface of the box; (3) give skates to the parts in the box in the amount of 2 pcs/column; (4) adding a rust category to the Q-point to be posted in the production and checking area. After carrying out these improvement actions, the number of defects in the products produced decreased and this was indicated by an increase in the sigma value from 3.6% to 3.9%.